2012
DOI: 10.1186/1471-2474-13-105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epimedium pubescen flavonoid on bone mineral status and bone turnover in male rats chronically exposed to cigarette smoke

Abstract: BackgroundEpimedii herba is one of the most frequently used herbs in formulas that are prescribed for the treatment of osteoporosis in China and its main constituent is Epimedium pubescen flavonoid (EPF). However, it is unclear whether EPF during chronic exposure to cigarette smoke may have a protective influence on the skeleton. The present study investigated the effect of EPF on bone mineral status and bone turnover in a rat model of human relatively high exposure to cigarette smoke.MethodsFifty male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…The O-phenolic group of flavonoids B ring poses as a hydrogen donor to receive free radicals and generated stable intramolecular hydrogen bonds with semiquinoid free radicals and thus blocking the free-radical chain reaction [37]. It has been reported that flavonoids can promote the proliferation and migration of adrenocortical stem cells and upregulate some growth hormones to improve animal growth and prevent the adverse effects of smoke exposure on bone by stimulating bone formation [38,39]. Noticeably, our results indicated that 70% EEFs represented dramatically DPPH free-radical-scavenging activity and could improve the growth performance and in vivo antioxidant of broilers, whereas the complex interplay between alfalfa flavonoids and in vivo antioxidant involved broilers fed with the different dose of 75% EEFs for 28 and 56 d needed to further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The O-phenolic group of flavonoids B ring poses as a hydrogen donor to receive free radicals and generated stable intramolecular hydrogen bonds with semiquinoid free radicals and thus blocking the free-radical chain reaction [37]. It has been reported that flavonoids can promote the proliferation and migration of adrenocortical stem cells and upregulate some growth hormones to improve animal growth and prevent the adverse effects of smoke exposure on bone by stimulating bone formation [38,39]. Noticeably, our results indicated that 70% EEFs represented dramatically DPPH free-radical-scavenging activity and could improve the growth performance and in vivo antioxidant of broilers, whereas the complex interplay between alfalfa flavonoids and in vivo antioxidant involved broilers fed with the different dose of 75% EEFs for 28 and 56 d needed to further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al 4 found similar results after 4 months of exposure to tobacco smoke. The literature shows that metabolic acidosis may negatively impact bone metabolism 2 .…”
Section: Discussionmentioning
confidence: 71%
“…Another fact that can be considered is that bone maturation only occurs after the 8th month of life in rats, 4 indicating a future possibility to investigate growth after the 8th month to assess the extent of the effect passive chronic smoking associated with swimming exercise has on a larger group of animals.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that nicotine affects the formation of bone due to the damage to the signaling pathways and metabolism associated with the extracellular matrix (24). It has also been reported that Gao et al (25) the exposure of male Wistar rats to cigarette smoke for 4 months, due to an increase in the levels of osteoclasts and decreased volume of bone connective tissue, the number and thickness of the connective tissue bands, the rate of bone formation, and the reconstruction of osteoblasts reduced the process of bone turnover. The increase in reactive oxygen species and free radicals due to smoking is also associated with the inhibition of the formation of osteoblasts in the bone surface (26).…”
Section: Discussionmentioning
confidence: 97%